2012
DOI: 10.1016/j.memsci.2011.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Development of a hydrophilic polymer membrane containing silver nanoparticles with both organic antifouling and antibacterial properties

Abstract: 1 Zeolites were added to polyethersulphone (PES) membranes in order to enhance their capability of attracting creatinine. Zeolite was blended with PES by varying its doping concentration and time, and the mechanical properties of the resulting hollow fibre membranes produced under optimal concentration were characterised. The values of tensile stress, tensile strain and Young's modulus, as well as the flux and rejection of the membranes were determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
119
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 266 publications
(121 citation statements)
references
References 32 publications
0
119
0
2
Order By: Relevance
“…A number of studies have reported on the incorporation of NPs in membranes and subsequent applications, for example, in water and wastewater treatment [3][4][5]. All these studies reported the significant enhancement membrane performance in terms of antifouling and antibacterial properties [6,7]. Recent work has reported on the membrane modification using ZnO NPs.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have reported on the incorporation of NPs in membranes and subsequent applications, for example, in water and wastewater treatment [3][4][5]. All these studies reported the significant enhancement membrane performance in terms of antifouling and antibacterial properties [6,7]. Recent work has reported on the membrane modification using ZnO NPs.…”
Section: Introductionmentioning
confidence: 99%
“…Various nanofillers including ZnO [20,21], TiO 2 [22,23], Al 2 O 3 [24,25], ZrO 2 [26,27], boehmite [28,29], silver [30,31], and CNTs [32,33] were employed to improve the performance of MMMs. CNTs are prominently employed due to their mechanical and chemical stability and adsorption capability.…”
Section: Introductionmentioning
confidence: 99%
“…15 Ion exchange capacity (IEC) and the degree of sulfonation (DS) of the prepared SPEEK were determined by H + release amount. For this, minced SPEEK ($1 g) was suspended in 2 M NaCl solution (100 mL) for 24 h. The resulting solution was titrated using 0.1 M NaOH solution with phenolphthalein as indicator.…”
Section: Peek Sulfonationmentioning
confidence: 99%